FINANCIAL DEVELOPMENT AND FOREIGN DIRECT INVESTMENT: THE ROLE OF INSTITUTIONAL QUALITY AS A MODERATION VARIABLE - Wasni Maisarah; Darmawati; Ghazali Syamni (CV. Radja Publika, 2024)
This research aims to determine the influence of Market Capitalization, Stock Index, Tax Rate, Gross Domestic Gross, Population and Institutional Quality on Foreign Direct Investment in ASEAN. And also to find out whether Institutional Quality strengthens the relationship between Market Capitalization, Stock Index, Tax Rate, Gross Domestic Gross, Population and Foreign Direct Investment in ASEAN. This research uses secondary data accessed on the official website of The World Bank and investing.com. Data processing uses eviews 10 software and this research uses panel data regression analysis. The research results show that Market Capitalization has a negative and significant effect on FDI, Market Capitalization has a negative and significant effect on FDI. Stock Index, Tax Rate, GDP, and Population have a positive and significant effect on FDI. Institutional Quality has a negative and significant effect on FDI. Institutional Quality does not have a significant effect in moderating Market Capitalization, GDP and Population on FDI. Institutional Quality has a significant effect in moderating the Stock Index and Tax Rate on FDI.